(untitled) (Jurnal Manajemen Bisnis, 2025)
In the current digital landscape, social media has emerged as one of the most effective and efficient online marketing tools. Among the widely used platforms today is TikTok, which now offers the TikTok for Business feature that enables companies to promote and showcase their products. Celebrity endorsers play an important role in supporting product promotion by creating engaging and creative content through their TikTok accounts. Additionally, product quality remains a crucial factor considered by consumers when making purchase decisions. This study aims to examine the influence of TikTok social media marketing, celebrity endorsers, and product quality on purchase decisions for Jiniso products, with trust in endorsers as a mediating variable. The research employs a descriptive quantitative approach using purposive sampling and non-probability sampling techniques. The descriptive results indicate that all variables demonstrate strong percentage scores. Hypothesis testing shows that TikTok social media marketing, celebrity endorsers, and product quality each have a positive and significant partial effect on purchase decisions. Furthermore, trust in endorsers moderates the relationship between TikTok social media marketing and purchase decisions; however, it does not moderate the relationship between celebrity endorsers and product quality toward purchase decisions.